Estimación del efecto Mohring en el sistema de transporte masivo Pumakatari de la ciudad de La Paz - Fabricio Fernando Iba\~nez Veizaga; Lourdes M. Espinoza Vásquez (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2016)
– The current documents attempts to establish the possible presence of the "Mohring" effect on the Pumakatari mass transport system created by the Municipal Government of La Paz on 2014. It begins estimating the utility function, as established on the theory of discreet elections and McFadden's theory of random utility (1974) , which incorporates differences on the trip costs , times and wait times as well as the socio economical characteristics of an user group. As a result, three Probit models are estimated with two alternatives Pumakatari Bus and other transport.
Keywords: L91; L92; R40; R41; 330; Mohring Effect; Transport System; Random Utility